Direct Inhibition of GSDMD by PEITC Reduces Hepatocyte Pyroptosis and Alleviates Acute Liver Injury in Mice - Wang, Jie; Shi, Ke; An, Ning; Li, Shuaifei; Bai, Mei; Wu, Xudong; Shen, Yan; Du, Ronghui; Cheng, Jingcai; Wu, Xuefeng; Xu, Qiang (Frontiers in Immunology, 2022)
Acute liver injury (ALI), often caused by viruses, alcohol, drugs, etc., is one of the most common clinical liver diseases. Although pyroptosis plays an important role in ALI, there is still a lack of effective clinical drugs related to this mechanism. Here, we show that phenethyl isothiocyanate (PEITC), a natural compound present in cruciferous vegetables, can significantly alleviate concanavalin A (ConA)-induced inflammatory liver damage and carbon tetrachloride (CCl4)-induced chemical liver damage in a dose-dependent manner. PEITC dose-dependently reversed the ALI-induced increase in plasma levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT), lactate dehydrogenase (LDH), tumor necrosis factor (TNF)-α and interferon (IFN)-γ and reduced the protein levels of hepatocyte pyroptosis markers such as Nod-like receptor family pyrin domain containing 3 (NLRP3), cleaved caspase-1, and cleaved gasdermin D (GSDMD). In vitro experiments have also verified the inhibitory effect of PEITC on hepatocyte pyroptosis. Furthermore, PEITC inhibits pyroptosis by interacting with cysteine 191 of GSDMD. In summary, our findings establish a role for PEITC in rescuing hepatocyte pyroptosis via direct inhibition of GSDMD, which may provide a new potential therapeutic strategy for ALI.